1986
DOI: 10.1126/science.3006244
|View full text |Cite
|
Sign up to set email alerts
|

Replicative and Cytopathic Potential of HTLV-III/LAV with sor Gene Deletions

Abstract: The genome of the human T-lymphotropic virus type III (HTLV-III/LAV) has the potential to encode at least three polypeptides in addition to those encoded by the gag, pol, and env genes. In this study, the product of the sor (short open reading frame) region, which overlaps the 3' end of the pol gene, was found to be a protein with a molecular weight of 23,000. An assay was developed for testing the ability of cloned HTLV-III proviruses to produce viruses cytopathic for T4+ lymphocytes. In the cell line used, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
120
2
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 208 publications
(131 citation statements)
references
References 44 publications
8
120
2
1
Order By: Relevance
“…The regulatory protein Nef has been suggested to induce apoptosis through a serine/threonine kinase-dependent signaling pathway (42). Studies of HIV-1 deletion mutants, however, have demonstrated that the expression of these regulatory proteins is either not necessary or insufficient for the major cytopathic effects of virus infection (14,45,47). Rather, the HIV-1 envelope glycoproteins apparently mediate most of the acute cytotoxic consequences accompanying virus production in the infected cell.…”
Section: Human Immunodeficiency Virus Type 1 (Hiv-1) Infection Of Hummentioning
confidence: 99%
“…The regulatory protein Nef has been suggested to induce apoptosis through a serine/threonine kinase-dependent signaling pathway (42). Studies of HIV-1 deletion mutants, however, have demonstrated that the expression of these regulatory proteins is either not necessary or insufficient for the major cytopathic effects of virus infection (14,45,47). Rather, the HIV-1 envelope glycoproteins apparently mediate most of the acute cytotoxic consequences accompanying virus production in the infected cell.…”
Section: Human Immunodeficiency Virus Type 1 (Hiv-1) Infection Of Hummentioning
confidence: 99%
“…SW480 and lymphoid cells were transfected with uncleaved plasmid DNAs by the calcium phosphate coprecipitation (Adachi et al, 1986) and the DEAE-dextran (Sodroski et al, 1986) methods, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In order to infect nonpermissive cells containing A3G or -F, HIV-1 has evolved the HIV-1 viral infectivity factor (Vif), a 23-kDa basic protein (13) required for in vivo viral propagation and pathogenesis (14)(15)(16). Vif has been shown to efficiently counteract the antiviral activity of A3G and -F by various mechanisms (1,17).…”
mentioning
confidence: 99%